Problems in joint management body for medium cost residential in Shah Alam / Nik Mohd Amiruddin Nik Mohd Alias - Nik Mohd Alias, Nik Mohd Amiruddin (Faculty of Architecture, Planning and Surveying, 2013)
Rapid urban development has led to significant increase in the demand for housing and related amenities. The scarcity of land for property development has led to the construction of more high-rise residential buildings. An increasing number of property buyers prefer the convenience and security offered by high rise condominiums, apartments and housing units developed under the concept of gated communities. As the development area for such housing involves the concept of sharing among owners and dwellers particularly for common properties, relevant lawsand regulations have been enacted recently publish is Act 663. Prior to Act 663, the laws pertaining to management and maintenance of buildings and common property were provided for under the Housing Development Act (Control and Licensing) 1966 [Act 118], the Housing Development Rules (Control and Licensing) 1989 and the Strata Title Act 1985 [Act 318]. Thus the objectives of the study are to find out what are common practices done by the apartment’s management and related parties after this past few years. It is also to find out what are the common problems faces by the JMB and to give suggestion that might serve as solution.